Validity and reliability of the Disabilities of Arm, Shoulder, and Hand scale in dental students: A transnational study - Wajngarten, Danielle [UNESP]; Campos, Juliana Alvares Duarte Bonini [UNESP]; Botta, Ana Carolina; Nordi Sasso Garcia, Patrícia Petromilli [UNESP] (Taylor & Francis, 2018)
This study aimed to evaluate the validity and reliability of the Disabilities of Arm, Shoulder, and Hand (DASH) scale in Brazilian and American dental students and assess the influence of demographic variables on disability in them. A cross-sectional observational study was conducted with a nonprobabilistic sample. The sample was composed of students of both genders from the School of Dentistry of Araraquara, State University of São Paulo (UNESP) (n = 288), and students from Stony Brook University, New York, NY, USA (n = 149). The disabilities of the upper limbs were estimated using the DASH scale. The samples were characterized by collecting information on gender, academic year, and sports and work activities. The refined bifactorial model presented goodness-of-fit indices for both countries. There was a significant effect of the variables gender and academic year for the Brazilian sample and the variable sports practices for the American sample. The refined bifactorial model was valid and reliable for the Brazilian and American populations. In this model, the removal of item 17 for the Brazilian sample and items 3, 13, and 23 for the American sample was necessary. Demographic variables such as gender, academic year, and sports practice contributed significantly to the level of disability in the study populations.
Keywords: DASH; dental students; ergonomics; musculoskeletal disorders; upper extremity